Polysemy of the Temporal Adverb JAM in Latin - Nataliia Panchyshyn (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
One of the most important types of semantic relations in the lexical and semantic system of languages is polysemy. The study of polysemy in Latin is extremely relevant, as it helps to understand the origin and development of polysemy in European languages that based on it.